DESIGNING PALEMBANG'S TYPICAL CULINARY INFORMATION SYSTEMS BASED ON WEBSITE AND SOCIAL MEDIA - Yudha Wahyu Hidayat; Leon A. Abdillah; Imam Prayuda; Ahmad Joko Kusumo; Desta Uda Pranata; Muhammad Syarriansyah (Sistemasi: Jurnal Sistem Informasi, 2020)
Information technology has opened up digital economic opportunities in Indonesia. A number of applications of information technology are the internet, websites and social media. The internet has become a medium of data and information traffic with very large capacities and very high speeds. Website can be used as virtual places for various purposes. Social media can be used as an online social media. Small and medium businesses are one of the pillars of national economic growth. But with the existing limitations, the small and medium-sized businesses (SMEs) actors/officers are still constrained by the promotion of their products. All the facilities and advances in information technology need to be packaged in such a way that they can be utilized by SMEs in running their business. This research will design a Palembang culinary information system website. The method used is web engineering which consists of 5 (five) phases: communication, planning, modeling, construction, and dissemination. The results of this study are in the form of web prototype Palembang's culinary information system that can provide information about Palembang's culinary products for social media-based SMEs.